An overview of treatment options for patients with relapsed/refractory multiple myeloma and renal impairment. (April 2022) - Dimopoulos, Meletios A.; Mikhael, Joseph; Terpos, Evangelos; Leleu, Xavier; Moreau, Philippe; Bladé, Joan; Kim, Jin Seok; Stockerl-Goldstein, Keith; Richardson, Paul G.
Renal impairment (RI) is a relatively common complication of multiple myeloma, which increases in frequency as disease becomes more advanced and recovery of renal function becomes less likely as patients progress through lines of therapy. Clinical trials in the relapsed/refractory multiple myeloma (RRMM) setting have not uniformly included patients with RI or robustly reported their outcomes. Here, we review existing data among patients with RI and RRMM across drug classes (including immunomodulatory agents, proteasome inhibitors, monoclonal antibodies, antibody-drug conjugates, chimeric antigen receptor T-cell therapies, and exportin-1 inhibitor) to provide an improved understanding of available treatment options for this important population. We highlight data from pivotal clinical trials, including data relating to renal response (as defined by the International Myeloma Working Group) and discuss real-world experiences in patients with RI, where applicable. Despite substantial advances in RRMM treatment, the presence of RI remains associated with reduced overall survival. Consistent inclusion of patients with RI, and uniform reporting of their outcomes, should be encouraged in future prospective trials of treatments for RRMM.